Development and African philosophy a theoretical reconstruction of African socio-political economy (New York iUniverse, 2004)
Development and African Philosophy explores the basis for rationalization of African social and political economy of development. It examines the theories, and Western logic of development, practically exemplified in the colonial ideology; hence it puts into perspective the developmental imperatives of Europe in Africa. Going beyond the logic of colonialism and an appeal to it by African leaders to hide their incompetence in leading their people, this book offers a broader view of development within the spectrum of philosophy. By using the conceptual tools of right, communion, covenant and initiative-democracy, it lays the foundation for a theoretical reconstruction of the African social and political economy by claiming that a philosophy of right and covenant can offer a key to economic and leadership problems in the management of peoples, resources and economies."Congratulations again on a great work A good and useful thesis."-Mons Bernard A Prince, Rome, Italy."Development and African Philosophy is a very provocative venture. After reading the work, several thoughts come to mind. It is no longer sufficient to view Philosophy and philosophical thoughts outside the realm of pressing needs of society. Dr Njoku's careful trace of the role of the concept of development in the history of Philosophy and there from attempt to create a new understanding of the concept of development suitable to Africa and African situation are a genial loop Dr Njoku's covenanted leadership and authority model could perhaps become the breakthrough for new understanding of democracy in African politics. It will surely need the test of time for credibility
Includes bibliography
Keywords: Development